(untitled) (Acta Entomologica Serbica, 2020)
After the first observations of cicadas of the subfamily Typhlocybinae (Hemiptera: Auchenorrhyncha: Cicadellidae), a specific white-orange-red coloration in Zrenjanin and Melenci in 2017 and 2018, four females of the same habitus were collected in August 2019 in Belgrade and Special Nature Reserve “Deliblato Sands”. External morphology analyzes indicated that they are most similar to the East Asian invasive species present in Europe, Tautoneura polymitusa Oh & Jung 2016. Due to the lack of sampled males, reliable species determination required the use of molecular methods. Since no nucleotide sequences of the barcoding region of the COI gene of the T. polymitus species are available in gene banks, specimens of males collected in Budapest at the site of the first find of the species in Europe were attached to the genetic identification. After successful multiplication and sequencing of the COI barcoding region, 100% genetic matching of the sequences of the analyzed females from Serbia and males from Hungary was determined. The obtained results confirm the presence of allochthonous cicada T. rolymitus in Serbia and indicate the importance of the barcoding method which in the context of biodiversity research successfully overcomes sampling problems such as small number of specimens or absence of males.